2011
DOI: 10.1002/anie.201102012
|View full text |Cite
|
Sign up to set email alerts
|

Rendering Schrock‐type Molybdenum Alkylidene Complexes Air Stable: User‐Friendly Precatalysts for Alkene Metathesis

Abstract: A matter of convenience: Schrock molybdenum alkylidenes are amongst the most powerful olefin metathesis catalysts known to date, but their sensitivity to air and moisture mandates their handling in a glove-box or by Schlenk techniques. This inconvenience is circumvented by using the corresponding phenanthroline- or bipyridine adducts, which are bench-stable and hence very user-friendly. The active species can be liberated from these precatalysts in uncompromised form on treatment with ZnCl2 in tolue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 40 publications
(22 reference statements)
0
57
0
Order By: Relevance
“…Recently, the Schrock catalysts have been rendered significantly more bench stable through complexation with 2,2 0 -bipyridine. 136 This practical advance will facilitate the use of these catalysts in synthetic laboratories. For RCEYM, the reactivity issue has been solved through tailored catalyst design.…”
Section: Ring-closing Applications With the Molybdenum Carbene Catalystsmentioning
confidence: 99%
“…Recently, the Schrock catalysts have been rendered significantly more bench stable through complexation with 2,2 0 -bipyridine. 136 This practical advance will facilitate the use of these catalysts in synthetic laboratories. For RCEYM, the reactivity issue has been solved through tailored catalyst design.…”
Section: Ring-closing Applications With the Molybdenum Carbene Catalystsmentioning
confidence: 99%
“…vi Eighteen electron Mo(NAr)(CH 2 )[OC(CF 3 ) 2 Me] 2 (bipy) is inactive as a metathesis catalyst and stable toward bimolecular decomposition reactions. Fürstner has reported that bipyridine adducts of several related molybdenum species are relatively stable to air and can be activated toward metathesis in the absence of air in solution through addition of ZnCl 2 to remove bipyridine; viia apparently little exchange of alkoxide for chloride on the molybdenum is observed during the activation process. He also has reported examples of 18 electron alkylidyne complexes that are relatively stable in air and can be activated through addition of Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…He also has reported examples of 18 electron alkylidyne complexes that are relatively stable in air and can be activated through addition of Lewis acids. viib Other types of 18 electron alkylidene complexes that are activated upon addition of Lewis acids are known. viii …”
Section: Introductionmentioning
confidence: 99%
“…Complexes 10 and 11 compare favorably with a few of the recently published catalyst complexes [19,35e38], but are on the other hand not significantly better than the most active catalysts [12,22,39,40]. Nonetheless it has to be conceded that the concept of this work (i.e.…”
Section: Evaluation Of the Electronic Properties Of Nhc 3 By Ir And Cmentioning
confidence: 80%